Relação professor-materiais curriculares em Educação Matemática: uma análise a partir de elementos dos recursos do currículo e dos recursos dos professores - Santana, Kátia Cristina Lima (2017)
In this study, our aim was to analyze and reflect on the teacher-curriculum material relationship from elements that make up the curriculum resources and resources of teachers who teach math. We propose to investigate what relationships can be established between teachers and math curriculum materials. Taking as theoretical contributions the studies on the teacher-curriculum material relationship, the Didactic-Mathematical Knowledge model of the teacher and studies on curriculum materials analysis, we developed an investigation that uses a qualitative methodological approach from the perspective of theoretical study of bibliographic research type and meta-analysis. The meta-analysis was carried out from the report of a research project in which teachers of the São Paulo municipal education evaluated the curriculum materials used by them to plan and develop their classes. The elaborated categories emerged from the data themselves. The thesis is organized in a multipaper format, composed of an introductory chapter, three articles and a chapter with final considerations. The results indicate that the teacher-curriculum material relationship involves a "two-way street: teachers mobilize their knowledge to interpret, understand and collaborate with curriculum resources, reconcile their perceptions of the original objectives of the materials with their own purposes and make decisions about the use, whether by reproduction, adaptation or improvisation. These decisions may be intentional or unconscious; sometimes they approach the original ideas, sometimes they move away from them. In the other way, the curriculum materials can offer opportunities, from elements and characteristics that favor the mobilization of knowledge of teachers who teach math. Teaching knowledge mobilized refer to the mathematical and didactic dimensions of Didactic-Mathematical Knowledge, especially in the epistemic and cognitive categories, with emphasis on the epistemic category. This result evidences that the inclusion, in curriculum materials, of elements that involve these categories of teaching knowledge, combined with the formations that could study and analyze the materials used by the teachers, favor the mobilization of their knowledge and can promote the change of some classroom practices by the teachers